2023
DOI: 10.3390/antibiotics12030432
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Ampicillin plus Ceftriaxone Combined in Elastomeric Infusion Devices for Outpatient Parenteral Antimicrobial Therapy

Abstract: Currently, ampicillin plus ceftriaxone (AC) is one of the preferred treatments for Enterococcus faecalis infective endocarditis. However, there is a lack of stability data for the combination of both drugs in elastomeric devices, so the inclusion of AC in Outpatient Parenteral Antimicrobial Therapy (OPAT) programs is challenging. The objective of the study was to determine the stability of AC in elastomeric pumps when stored at 8 ± 2 °C, 25 ± 2 °C, 30 ± 2 °C and 37 ± 2 °C using LC-MS/MS. The combination was di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Therefore, our data support that of Huskey et al [ 15 ], showing that the chemical stability of AMP is not compromised at the end of the 24 h infusion period at 25 °C after a refrigerated storage period of 72 h. Data regarding stability of diluted AMP solutions at 25 °C are more variable. At 20 mg/mL, AMP remained stable for 8 h [ 14 ], whereas at 24 mg/mL stability was maintained for 24 h [ 19 ]. Another study with 30 mg/mL AMP reported >90% concentration after 72 h [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, our data support that of Huskey et al [ 15 ], showing that the chemical stability of AMP is not compromised at the end of the 24 h infusion period at 25 °C after a refrigerated storage period of 72 h. Data regarding stability of diluted AMP solutions at 25 °C are more variable. At 20 mg/mL, AMP remained stable for 8 h [ 14 ], whereas at 24 mg/mL stability was maintained for 24 h [ 19 ]. Another study with 30 mg/mL AMP reported >90% concentration after 72 h [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous results for the stability of concentrated AMP solutions at warm temperatures have clearly shown what is already known: excessive drug degradation of >10% during the first 24 h [ 20 , 21 ]. A recent study with 24 mg/mL AMP reported stability >90% for the initial 24 h at 30 °C, but these EIPs did not undergo a previous refrigerated storage period [ 19 ]. Likely, similar results are expected to be reported by us and others, eventually leading us to draw the same conclusion: the stability of AMP solutions at temperatures above 25 °C is not guaranteed long enough to be used in OPAT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a very precise technique [ 203 ] we demonstrated the stability of this combination that we believe it would be an excellent alternative (much less toxic) to the A + G regimen, which is still used as a reference. Continuous or intermittent administration (every 4 h) of both drugs would always maintain levels above the required thresholds, without requiring any extraordinary manipulation other than periodic pump refilling [ 204 , 205 ] and have demonstrated excellent results in a few patients [ 196 ].…”
Section: Outpatient Parenteral Antimicrobial Therapy (Opat)mentioning
confidence: 99%
“…However, using a very precise technique 199 , we demonstrated the stability of this combination that we believe it would be an excellent alternative (much less toxic) to the A + G regimen, which is still used as a reference. Indeed, continuous or intermittent administration (every 4 hours) of both drugs would always maintain levels above the required thresholds, without requiring any extraordinary manipulation other than periodic pump refilling 200,201 .…”
Section: Outpatient Parenteral Antimicrobial Therapy (Opat) With the ...mentioning
confidence: 99%